2009
DOI: 10.1038/tpj.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

The modulating effect of the androgen receptor on craving in alcohol withdrawal of men is partially mediated by leptin

Abstract: We reported recently that a functional relevant CAG trinucleotide repeat of the androgen receptor influences craving of men in alcohol withdrawal. It is known to modulate serum concentrations of leptin, which affects hypothalamic appetite regulation. Its plasma levels are elevated during chronic alcohol consumption, normalize within periods of abstinence and are associated with craving. The aim of this study was to further elucidate the role of leptin in mediating the effects of the mentioned polymorphism on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
(88 reference statements)
2
9
0
Order By: Relevance
“…In human cells in vitro demethylation of the promoter leads to an increase of leptin expression (Melzner et al, 2002). There are different other mechanisms that influence leptin expression in humans like the function of the androgen receptor as transcription factor (Lenz et al, 2010). Our results are in line with these findings showing a significant inverse association between mean promoter methylation and changes of leptin serum levels during withdrawal.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In human cells in vitro demethylation of the promoter leads to an increase of leptin expression (Melzner et al, 2002). There are different other mechanisms that influence leptin expression in humans like the function of the androgen receptor as transcription factor (Lenz et al, 2010). Our results are in line with these findings showing a significant inverse association between mean promoter methylation and changes of leptin serum levels during withdrawal.…”
Section: Discussionsupporting
confidence: 89%
“…Results on leptin serum levels from this study population have been included in different analyses (Kraus et al, 2004;Hillemacher et al, 2007a,b;Lenz et al, 2010Lenz et al, , 2012. All study participants gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Lenz et al . [35] have suggested that androgen receptor on craving in alcohol withdrawal in men is partially mediated by leptin. Thus, the relationship between craving scores and NUCB2/nesfatin-1 level according to gender seems to be unclear and needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…A significant inverse relation was reported between total and obsessive craving and androgen receptor repeat length such that a greater number of length of repeats was significantly associated with attenuated severe craving in men (Lenz et al 2009). A subsequent study on this group of men in alcohol withdrawal also reported that this polymorphism mediates its effect on craving primarily through regulation of leptin (Lenz et al 2010). …”
Section: Reproductive Hormonesmentioning
confidence: 90%